Wireless Fall Warning System with Real-Time Motion Monitoring - Pham, Ngoc Phuc; Nguyen, Hieu Duc; Nguyen, Diep My; Tran, Vi Quoc; Do, Quan Van; Pham, Hung Manh (Old Journal, 2019)
Fall is one of the major causes of serious injury, which include fractures, traumatic brain injury, and death to the elders or people who live alone. A wearable fall detection system is becoming a potential solution thanks to its popular accelerometer sensor and easily implementation. In this study, we proposed a design and implementation of wireless fall warning system with real – time motion monitoring. The wearable motion sensor module received real-time human motion is used in combination with a smartphone through wireless Bluetooth connection. A Fall warning application on smartphone is responsible for wirelessly send fall warning message of subject through GSM service and Google map – based fall location. The implementation of our proposed system shows a great potential solution in supporting elders, decreasing deaths and improve their lives qualities.